Aggressive behavior and its relationship to skill performance efficiency of Kirkuk youth football players - Ali, Ammar Majeed; Mohammed, Dlawar Anwer; Hasan, Marwan Abdulnbi (Universitas Tanjungpura, 2026)
Background. Aggression is a common event in any football match, especially with young footballers who lack self-control and a high level of psychological maturity. As a result, it is necessary to study the relationship between the components of aggressive behavior and the efficiency of skill performance to have an evidence-based approach to youth football training. Objectives. The objectives of this study were to assess the level of aggressive behavior and the efficiency of the skill performance of junior football players at clubs in Kirkuk Governorate. Methods. The research design of this study was descriptive correlational. The study sample included 121 junior players selected from the six first division football clubs at Kirkuk Governorate during the 2023 competition. A multidimensional sports aggression questionnaire was used to measure the level of aggressive behavior, and the efficiency of the skill performance was measured by the available performance indices. The analysis was assisted using SPSS version 26. Results. The results of the study showed that there was a significant statistical relationship between the overall score of aggressive behavior and the efficiency of the skill performance. The domain of hatred did not have a significant statistical difference with the efficiency of the performance than other domains of aggressive behavior. This means that being aggressive due to hatred toward an opponent is not a common case that can directly affect the performance of junior footballers in Kirkuk governorate. Conclusion. This study is unique to present primary evidence of aggression among junior football players in Kirkuk Governorate, where aggression is a cross-cultural issue in sports. The results of the present study supported the integration of well-structured psychological preparation with physical and technical training to improve performance efficiency and reduce dysfunctional aggressive behavior among junior football players.